Facile Synthesis of Protonated Carbon Nitride/Ti3C2Tx Nanocomposite for Simultaneous Detection of Pb2+ and Cd2+. Issue 6 (20th March 2020) - Lv, Xuchu; Pei, Fubin; Feng, Shasha; Wu, Yi; Chen, Shen-Ming; Hao, Qingli; Lei, Wu
Abstract : A high-sensitivity electrochemical sensor for heavy metal ions (HMIs) was prepared by associating Ti3 C2 T x with protonated carbon nitride (H–C3 N4 /Ti3 C2 T x ). Due to the electrostatic interaction, massive H–C3 N4 was distributed on the surface of Ti3 C2 T x and served as coating material. H–C3 N4 /Ti3 C2 T x composite showed great conductivity derived from Ti3 C2 T x, and H-C3 N4 was with abundant electroactive deposition sites for the deposition of HMIs. In addition, the stability of H–C3 N4 /Ti3 C2 T x composite was enhanced due to the protective H–C3 N4 coating. The H–C3 N4 /Ti3 C2 T x electrode exhibited remarkable sensitivities for the simultaneous detection of Cd 2+ (0.05 ∼ 1.50 μ M) and Pb 2+ (0.05 ∼ 1.50 μ M) and the detection limit of Cd 2+ and Pb 2+ were 0.001 and 0.0006 μ M, respectively. Notably, sensor based on H–C3 N4 /Ti3 C2 T x composite showed excellent selectivity for Cd 2+ and Pb 2+ in the presence of interfere ions and molecules (K +, Na +, Ca 2+, Hg 2+, Cr 2+, Cu 2+, Cl −, NO3 −, PO4 −, ascorbic acid, uric acid, acetaminophen, glucose and nicotinamide). Besides that, distinguished stability and reproductivity of H–C3 N4 /Ti3 C2 T x electrode indicate that this sensor is promising for HMIs in wastewater and other commercial applications.